Answer :

2x + 3 = 3x – 3


3x - 2x = 3 + 3


x = 6


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)